2013
DOI: 10.1007/s10072-013-1571-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of headache in patients with Parkinson’s disease and its association with the side of motor symptom onset

Abstract: We compared the lifetime prevalence and the prevalence of headache during the previous year in patients with Parkinson's disease (PD) and control subjects. We also investigated the association between the side of PD symptom onset and the side of the headache. We interviewed 98 consecutive patients with an established diagnosis of PD between December 2010 and January 2012. The control group consisted of the 98 oldest sex-matched individuals from the nationwide Brazilian headache database. PD patients showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 22 publications
3
14
2
1
Order By: Relevance
“…The findings of the current study are inconsistent with those of previous clinic-based observational studies, which have demonstrated no significant difference [ 18 ] or a lower prevalence of headache [ 17 , 19 ] in sex- and age-matched PD patients and controls. This discrepancy warrants careful consideration and interpretation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of the current study are inconsistent with those of previous clinic-based observational studies, which have demonstrated no significant difference [ 18 ] or a lower prevalence of headache [ 17 , 19 ] in sex- and age-matched PD patients and controls. This discrepancy warrants careful consideration and interpretation.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to these studies, Lorentz et al identified no significant differences in the total prevalence of headache among PD patients in a controlled study [ 18 ]. Furthermore, a later study demonstrated that PD patients had a lower lifetime prevalence of headache than control subjects did [ 19 ]. Previous studies have focused on the relationship between migraine and PD, and a prior validation study reported that 80% of individuals with non-migrainous headache might have TTH [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies compared PD patients with and without headache and found that the 2 groups were similar in terms of PD symptoms. 7,8 To our knowledge, no other study has compared neck stiffness with the severity of headaches. We had expected to find this association, but we did not.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant side of headache was ipsilateral to the side of the initial symptoms of PD in the majority of patients who had unilateral PD onset. 8 The aims of the present study were to evaluate the frequency and characteristics of headaches among PD patients and to compare the patients and headache characteristics between those whose headaches started after PD had been diagnosed and the other patients with headaches. We also evaluated whether there was any correlation between the PD motor symptoms and the severity of the headaches presented.…”
Section: Introductionmentioning
confidence: 99%
“…Kopfschmerzen sind bei Parkinson-Patienten seltener als bei Nichtparkinson-Patienten (38). Bei Patienten mit orthostatischer Hypotension und kombinierten Hinterhaupt-und bilateralen Schulterschmerz ist an den "coat hanger pain" zu denken, der nach Besserung der orthostatischen Hypotonie nachlassen sollte (28).…”
Section: Kopfschmerzenunclassified